Analisis Perubahan Luas Lahan Sawah Berkaitan Dengan Kebutuhan Luas Lahan Sawah Di Kabupaten Aceh Besar - R Rusmini (LPPM Universitas Malikussaleh – Indonesia, 2019)
Aceh Besar is one of the regency in Aceh Province which is the center of rice production who directly adjacent to the Banda Aceh regency which resulted in the conversion of rice fields for other uses. This study aims to (1) Identify wetland area in 2009 and 2014 in Aceh Besar spatially, (2) Analyze the need for wetland area in Aceh Besar and Banda Aceh to meet the needs of its population. This research was conducted from January to March 2017 in Aceh Besar. The data used was secondary data, which is obtained from related institutions. The obtained results of this study are: wetland area in 2009 as many as 19.234,05 Hectares and in 2014 as many as 19.055,79 Hectares. The result shows the change of wetland area of 178,28 Hectares and the transfer rate of function of V <0 which is equal to – 0,94%. The need for rice fields with the assumption of productivity is 1.87 tons/ha/year until 2034 covering an area of 22,267.96 hectares while the available land is 18,342.75 hectares of which rice production is used to meet the needs of the people of Aceh Besar and Banda Aceh with a population of 930,752 people, so that production experienced a deficit of 77,449.91 tons. The need of rice field is influenced by the population growth, rice grain needs, and rice grain production in ton/ha/year which influenced by the productivity and planting intensity